RELEVANSI KONSEP PENDIDIKAN ISLAM KH. AHMAD DAHLAN DI ABAD 21 - Putri Yuliasari (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2014)
The education according to Islam is the part of work for human to deresponsibly. In order that, Islam surely gives the basic concepts aboutan education and it becomes the responsibility for human to explicit byaplicating those basic concepts in the practice of education. One of theintelectual moslems which is trying to reconstruct the paradigm buildingthat can be a basic of National Education system is K.H Ahmad Dahlan.Referrring to that background, it can be attractted one problem related tothe thoughts of K.H Ahmad Dahlan about the concept of Islamic educationand the relevantion of K.H Ahmad Dahlan’s Thoughts to the concept ofIslamic education in age 21.The thought of K.H Ahmad Dahlan about the concept of Islamic Educationmay be seen from his efforts in integrating dichotomyof knowledge,keeping the balance, patterning intelectual, attitude and religious. The aimof Islamic education referring to him is to bear individu in whole. In theframework to integrate two sysstem of education, K.H Ahmad Dahlan moreadobts education system from western school which is on one step forward.The thought of K.H Ahmad Dahlan has a relevancy when it is faced to thecontext of Islamic education in age 21. The thought of K.H Ahmad Dahlanabout concept of Islamic education is the one of alternative ways that canbe realized to find the way of education problem in age 21